The Influence of Monetary Incentives, Teacher Competence, and Principal Leadership Style on Teacher Performance - Nova Rabi'ah Nurrochmah; Ronald Suryaputra; Asriana Kibtiyah (Journal of Educational Management Research, 2026)
Teacher performance is a critical determinant of educational quality, particularly in private schools that emphasize institutional effectiveness and accountability. This study aims to examine the effect of monetary incentives, teacher competence, and principal leadership style on teacher performance. A quantitative approach was employed using a causal research design to test the hypothesized relationships among variables. The study involved 60 teachers selected through a saturated sampling technique. Data were collected using structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS version 4. The results indicate that monetary incentives have a positive but not significant effect on teacher performance, while teacher competence and principal leadership style have positive and significant effects on teacher performance. Furthermore, the three variables simultaneously exert a significant influence on teacher performance. These findings imply that improving teacher performance should prioritize the enhancement of teacher competence and effective leadership practices rather than relying solely on financial incentives, thereby providing important insights for educational management and policy development in private educational institutions